Multiple scanning electrochemical microscopy mapping of tyrosinase in micro-contact printed fruit samples on polyvinylidene fluoride membrane. (10th October 2015) - Lin, Tzu-En; Cortés-Salazar, Fernando; Lesch, Andreas; Qiao, Liang; Bondarenko, Alexandra; Girault, Hubert H.
Abstract: Herein, we introduce three orthogonal and compatible methods for detecting tyrosinase, a key factor in fruit browning and skin disorders, with high spatial resolution by means of scanning electrochemical microscopy (SECM). All methods are performed subsequently on the same substrate area providing a wide range of relevant information. The first SECM approach that relies on the mapping of a differential pore oxygen concentration induced by the local hydrophobic changes that the adsorption of tyrosinase generates on a porous polyvinylidene fluoride (PVDF) membrane. The second approach is based on the direct monitoring of the enzymatic activity of tyrosinase by detecting amperometrically the reaction products from the enzymatic conversion ofl -3, 4-dihydroxyphenylalanine (l -DOPA). Finally, tyrosinase was visualized implementing a tyrosinase sandwich immunoassay readout by SECM. The multiple SECM detection strategies were successfully applied to map unequivocally the tyrosinase enzymatic activity of a micro-contact printed banana sample. Furthermore, differential pulse voltammetry and mass spectrometry analyses were employed to elucidate the nature of the electrochemical response obtained during the tyrosinase enzymatic activity experiments.